Alcune norme per un’anarchia della lingua: i manifesti d’improvvisazione del sottosuolo letterario russo (Itinera, 2015)
In this essay I will analyze some literary manifestos written within important artistic movements which developed in Russian literary underground context after the 1960s, as a reaction to the ideological absolutism pursued by the Soviet dictatorship. In particular, I will focus on the contrast, the fine boundary, and the connection between the strict form of the literary manifesto, made by a series of rules, and the experimental spontaneity and chaos enunciated by the manifestos themselves.